Multidimensional Deprivations and Associated Factors Among Older Adults in Urban Geographies of Nigeria: Implications for Poor Health Outcomes in Later Life - Jacob Wale Mobolaji (Frontiers Media S.A., 2024)
Objectives: Many urban-dwelling older Nigerians are multidimensionally deprived and are unable to meet their daily financial, nutritional, and healthcare needs. This has implications for their health outcomes, yet it has been under-researched. This study assessed the multidimensional deprivation index (MDI) of urban-dwelling older Nigerians and the associated factors.Methods: The study analysed a weighted sample of 5,225 older persons aged ≥60 years from Nigeria's Demographic and Health Survey, 2018. MDI was estimated, and associations were examined using a multilevel multinomial logistic regression model.Results: Nationally, 75% of the older persons were multidimensionally deprived, with 27% severely deprived. Women (36%) were more severely deprived than men (20%). Those in the Northern regions (38%-40%) were the most deprived. Higher MD risk was associated with female gender and older ages ≥70-79 years. Conversely, lower risk was associated with households headed by family and residence in educated communities. Community variation accounts for 10.4% and 35.9% of the MD and severe MD risks, respectively.Conclusion: This study suggests socioeconomic interventions that address gender disparities and target highly deprived regions, with consideration for individual and community characteristics.